Strategi Efektif Media Pembelajaran Dalam Menguasai Kosa Kata Bahasa Arab - Novien Rialdy; M. Irvan Maulana (Lembaga Pengembangan Kinerja Dosen, 2025)
This article looks at developments in learning to understand Arabic. The main aim of this article is to find out how effective learning tools are that focus on mastering knowledge first rather than improving other language skills. Vocabulary is very important to master Arabic. The problem raised is how effective media is in increasing mastery of Arabic vocabulary. The results of research and discussions show that this learning tool is very effective in improving Arabic language comprehension.